Manajemen Peserta Didik Melalui Hasil Tes StiFIn di Sekolah Menengah Pertama Nuris Jember - Muhammad Ferdi Faurandra; Nur Ittihadatul Ummah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to describe the application of StiFIn the results in student management at Nuris Junior High School (SMP) Jember. The StiFIn test is used by the school to identify students’ dominant intelligence as a basis for managerial decision-making. This study used a descriptive qualitative method with data collection techniques in the form of observation, interviews, and documentation. The results show that StiFIn is utilized in several key aspects, namely recruitment strategies, student placement and grouping, student service development, and achievement evaluations and coaching. The application of StiFIn test results helps the school understand the character and natural potensial of each student so that educational services can be provided more appropriately and personally. Overall, the us of StiFin has been proven to support the effectiveness of student management and improve the quality of learningand student development at Nuris Juniar High School Jember.